Early Cretaceous bivalves of the Romualdo Formation, Araripe Basin, northeastern Brazil - Guerrini, Vitor B.; Matos, Suzana A.; Fürsich, Franz; Rodrigues, Mariza G.; Varejão, Filipe G.; Warren, Lucas V.; Assine, Mario L.; Simões, Marcello G. (Cretaceous Research, 2024)
The fossil-rich Romualdo Formation (late Aptian/early Albian), Araripe Basin, northeastern Brazil, contains world-renowned Fossillagerstätten characterized by exceptionally preserved fossils. Macroinvertebrates in this formation are primarily represented by mollusks, echinoids, and decapod crustaceans. Mollusk shells are abundant in certain stratigraphic intervals, forming coquinas or shell pavements. Despite recent advances in our understanding of the taxonomy of certain groups, comprehensive taxonomic studies are lacking for almost the entire bivalve fauna. Therefore, a detailed taxonomic analysis is presented here. The described bivalves include four new genera (Araripenomia, Ciceromya, Inversatella, Australoeocallista), and six new species (Araripenomia infirma, Inversatella cearensis, Ciceromya edentulosa, Australoeocallista juazeiroi, Legumen kaririense, and Corbulomima delicata), in addition to Musculus maroimensis, Crassatella maroimensis, “Myrtea” sp. and “Tellina” sp. This bivalve fauna mainly consists of cosmopolitan and endemic brackish/marine genera, with Tethyan affinities. The fauna is not homogeneously distributed in the sedimentary succession of the Romualdo Formation, but is constrained to the third order highstand systems tract. Bivalves recorded from muddy facies are strongly dominated by infaunal and semi-infaunal suspension feeders. Assemblages of the sand-dominated facies, with dense shell accumulations of semi-infaunal to epifaunal byssate and infaunal suspension feeders, were formed under shallow, higher energy conditions. Despite the degree of generic endemicity, the mytilids, anomiids, crassateliids, astartids, tellinids, and corbulids are related to the bivalve fauna of the Early Cretaceous Riachuelo Formation of the Sergipe-Alagoas Basin, as previously demonstrated for the bakevelliids and echinoids. Indeed, the Romualdo bivalve fauna is, in part, a modified and impoverished brackish/marine fauna of the Riachuelo Formation.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Araripe Basin; Bivalve mollusks; Estiva; Lower Cretaceous; Santana Group; Sobradinho